Understanding Philosophy And Ideology Present Education - Lanny Laras; Daniel Tumbel (Jurnal Didaskalia, 2022)
Modern methods of education are structured on the basis of modern ideological and philosophical. Various methods of a human nature or humanism, make the human being the center or center of learning. Modern science has created a great many moral problems in the environment of modern society. It is generally worrying that modern education is influencing values to children. Moral values can be taught through literature and textbooks but nevertheless the atmosphere or atmosphere of learning also needs to be considered. The modern view considers that with the education of good ethical values, children will automatically turn out to be good. If the situation or environment is improved structurally and economically, education and good moral ethical values, then society will automatically also change for the better. Is that really the case? The reality that is happening in the world is very contradictory.